Factionalism in Southeast Asia: Types, Causes, and Effects. Issue 1 (April 2020) - Hicken, Allen; Tan, Netina
In this article we present an overview of the arguments contained in the articles of this special issue. We first catalogue the varieties or types of factionalism present across Southeast Asia—namely, programmatic, clientelistic, and personalist/charismatic. We then explore the question of why the degree and type of factionalism varies across countries, across time, and across parties. We first focus on differences between factionalism in governing and opposition parties, arguing that factionalism across dominant and opposition parties differs in terms of the origin, type, and effect. We find that the more competitive the party system the more likely it is that factional patterns between the parties within a given polity will converge. We then review the relative power of socio-structural and institutional explanations of factionalism, and place the greatest weight on the role of patronage, party size, and the degree of party centralization. Finally, we turn our attention to common strategies for curbing factionalism across our cases and conclude by examining the consequences of factionalism.